Cefiderocol for treatment of an empyema due to extensively drug-resistant Pseudomonas aeruginosa: Clinical observations and susceptibility testing considerations. (2020) - Kufel, Wesley D.; Steele, Jeffrey M.; Riddell, Scott W.; Jones, Zachary; Shakeraneh, Pegah; Endy, Timothy P.
Abstract: Cefiderocol is a novel siderophore cephalosporin antibacterial with activity against carbapenem-resistant Gram-negative bacteria including Pseudomonas aeruginosa . We report a medically complex patient treated with compassionate use cefiderocol for an empyema caused by extensively drug-resistant P. aeruginosa as well as clinical considerations for cefiderocol use based on our findings. We observed a potential discordance in cefiderocol susceptibility testing results depending if disk diffusion or iron-depleted cation-adjusted Mueller Hinton Broth dilution is used. Furthermore, interpretative criteria differ between the Clinical Laboratory Standards Institute and United States Food and Drug Administration for P. aeruginosa, which makes cefiderocol interpretation potentially challenging for clinicians. We may have also observed selective pressure from prior cefiderocol exposure given the respective increases and decreases in MIC values and zone diameters for P. aeruginosa isolates following cefiderocol treatment. Additional data are needed to further describe cefiderocol use, susceptibility testing, and resistance development as real-world clinical use expands.